Green Building Materials, Construction and Sustainability : special topic volume with invited peer-reviewed papers only - Muthusamy, Ramya; Sengodan, Thangaprakash; Morales-Palma, Domingo; Martínez-Donaire, Andrés J.; Borrego Puche, Marcos; Centeno Báez, Gabriel; Vallellano, Carpoforo (Key engineering materials ;, 2023)
This special collection is devoted to actual issues in developing machinery technologies and the implementation of sustainable development principles in the area of building materials and modern manufacture. The special edition will be useful to specialists in machinery and technologies of materials processing, development of green building materials and waste management activity. Welding, Friction Stir Welding, Alloy, Dissimilar Joint, Green Building Materials, Green Concrete, Mechanical Properties, Geopolymer, Ceramic Waste, Cement, Activated Slag, Additive Manufacturing, Tool, Carbon Footprint, Plant Cellulose, Waste Management Materials Science, Building Materials, Manufacturing.